2021
DOI: 10.3390/ijms22031406
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Modulation of Host Immune Response and Inflammation Triggered by Helicobacter pylori

Abstract: Helicobacter pylori (H. pylori) remains the most-researched etiological factor for gastric inflammation and malignancies. Its evolution towards gastric complications is dependent upon host immune response. Toll-like receptors (TLRs) recognize surface and molecular patterns of the bacterium, especially the lipopolysaccharide (LPS), and act upon pathways, which will finally lead to activation of the nuclear factor-kappa B (NF-kB), a transcription factor that stimulates release of inflammatory cytokines. MicroRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 96 publications
(127 reference statements)
0
26
0
Order By: Relevance
“…MiRNAs are among the molecules with an expression change that is very sensitive to microscopic alteration of gastric mucosal integrity. Most studies have, so far, investigated their behavioral pattern in relation to H. pylori infection, with miRNAs acting as fine modulators of the immune response triggered by the pathogen [ 12 , 20 , 31 , 32 ]. Expression alteration seems not to be definitive, with one study proving that eradication of H. pylori infection seems to restore expression of particular miRNA molecules to normal [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs are among the molecules with an expression change that is very sensitive to microscopic alteration of gastric mucosal integrity. Most studies have, so far, investigated their behavioral pattern in relation to H. pylori infection, with miRNAs acting as fine modulators of the immune response triggered by the pathogen [ 12 , 20 , 31 , 32 ]. Expression alteration seems not to be definitive, with one study proving that eradication of H. pylori infection seems to restore expression of particular miRNA molecules to normal [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have, however, been proven to play a role in various biologic processes and their dependence upon target gene expression translates into contradictory effects on different organs and tissues [ 11 ]. Given their proven role in the modulation of the innate and adaptative immune response, miRNAs are regarded as key regulators of inflammatory pathways triggered by pathogens such as H. pylori [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulating cholesterol synthesis, the virulence factors of H. pylori , and ROS responses, it is possible that statins reduce the risk of H. pylori -associated GC via the regulation of miRNAs and exosomes. For example, miRNA-146 and miRNA-155 are induced after H. pylori infection to regulate inflammation [ 76 , 77 ]. Another miRNA, let-7b is reduced in GC cells in a CagA-dependent manner, which may lead to the downregulation of TLR4 [ 78 ].…”
Section: Statins Modulate Micrornas and Exosome Levelsmentioning
confidence: 99%
“…It is well-documented that this infection might lead to chronic gastritis, peptic ulcers, gastric cancer, and mucosa-associated lymphoid tissue lymphomas [ 1 , 2 ]. It was previously demonstrated that H. pylori -associated inflammation is closely related to the host’s innate immune system since it is capable of triggering these responses via particular pathogenicity features such as cag-pathogenicity island (cagPAI) and vacuolating cytotoxin A (VacA), or pathogen-associated molecular patterns (PAMPs), involving flagellin and lipopolysaccharides (LPS) [ 3 , 4 ]. The combination of PAMPs, toll-like receptors (TLRs), and nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) results in the activation of immune cells receptors and subsequent promotion of both secretion and expression of several proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%